Comparison of quality of life of schizophrenic patients and healthy people in Rasht - naeima Khodadady; farzaneh shikholeslami; hayedeh mahmuodi; mojgan Baghaie; mahmuod hafezi (Guilan University of Medical Sciences, 2009)
Introduction: Schizophrenia is a common chronic psychiatric disease which can result in personal-‎social problems. Recently, quality of life (QOL) is considered as an important measure of the ‎impacts of schizophrenia and its treatment, and can be useful in proper planning.‎ Objective: The purpose of this study is to compare QOL in schizophrenic patients and healthy ‎people in Rasht city.‎ Methods: This study is a cross-sectional descriptive survey that was done on ‎‏52‏‎ patients with ‎schizophrenia visiting outpatient clinic in Shafa hospital which were selected by convenience ‎sampling. Also ‎‏153‏‎ healthy people in Rasht were selected randomly by cluster method. Data ‎collection instrument was a ‎‏3‏‎- part questionnaire consisting ‎‏1‏‎) personal-social questionnaire, ‎‏2‏‎) ‎WHO ‎‏28‏‎-item QOL questionnaire, and ‎‏3‏‎) mental status assess form. Third tool was specially used ‎for patient group. Data gathered by face-to-face interview and analyzed by SPSS. ‎ Results: The finding indicated that mean score of QOL and all of its domains consisting general, ‎physical, psychiatric, social relationship, and environmental was lower in schizophrenic patients ‎‎(‎‏83.03‏‎- ‎‏6.42‏‎- ‎‏22.19‏‎- ‎‏25.15‏‎- ‎‏6.22‏‎, and ‎‏23.05‏‎ respectively) comparing to healthy people ‎‎(‎‏90.49‏‎, ‎‏7.26‏‎, ‎‏25.87‏‎, ‎‏27.62‏‎, ‎‏7.16‏‎, and ‎‏23.19‏‎). There was statistically significant ‎difference between schizophrenic patient's and healthy people's QOL (P=‎‏0/0001‏‎), and it's general ‎‎(P=‎‏0/006‏‎), physical (P=‎‏0/0001‏‎), psychiatric (P=‎‏0/001‏‎), and social relationship (P=‎‏0/015‏‎) ‎domains according to independent-t test results. ‎ Conclusion: According to this result, schizophrenic clients, even with better mental status, have ‎lower QOL level than healthy people that need special attention to improve their post-discharge ‎treatment and care. ‎